Strategy For Improving Awareness And Legal Compliance In National Legal Guidance - Irwan Triadi; Indra Hendrawan; Ahmad Haris Junaidi; Dimas Yanuarsyah (International Journal of Law, Crime and Justice, 2024)
Legal awareness and compliance are fundamental pillars of national legal development, aimed at establishing a just, effective, and responsive legal system that aligns with societal dynamics and development needs. This study identifies strategies to enhance legal awareness and compliance at individual, institutional, and corporate levels through a normative juridical approach, analyzing key elements of the legal system—legal substance, legal structure, and legal culture—based on Lawrence Friedman’s theory. The research highlights the importance of legal audits as a strategic tool for assessing regulatory compliance and ensuring the implementation of Good Corporate Governance in public institutions and business entities. Strengthening the regulatory framework for legal audits, including legitimizing the legal auditor profession, is essential to ensure independent, objective, and credible assessments, fostering public trust, business confidence, and legal system stability. By bridging gaps between legal formulation and implementation, legal audits contribute to a conducive business environment, enhanced national competitiveness, and effective legal development that supports Indonesia’s vision as a secure, just, and prosperous state.